The role of social work in addressing the social and psychological dimensions of kidney failure patients: An applied study on a sample of kidney failure patients in the city of Benghazi - Salmeen Al-Fakhri, (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
This study aims to identify the role of social work in addressing the social and psychological dimensions associated with kidney failure. It seeks to analyze these dimensions, identify the prominent problems experienced by patients, and determine the professional intervention mechanisms of social work to mitigate their effects. Adopting a descriptive analytical approach, the study utilized a questionnaire as the primary tool for data collection from a random sample of 150 kidney failure patients in Benghazi. The investigation focused on variables including social adjustment, family relationships, social support, psychological status, and level of adaptation to the disease. The findings revealed that a majority of patients suffer from poor social adjustment, difficulties in performing family roles, and a decline in social participation, consistent with literature indicating feelings of isolation. Additionally, the results showed a high prevalence of psychological disorders, specifically anxiety and depression, stemming from the chronic nature of the disease and continuous treatment. Conversely, the study demonstrated that social work interventions play a pivotal and positive role in improving patients' quality of life, enhancing social adjustment, strengthening family relationships, and mitigating psychological pressures. Based on these outcomes, the study recommends strengthening the role of social workers within dialysis centers, providing structured psychological and social support programs, organizing educational initiatives for patients' families, and activating recreational activities to reduce isolation.
Keywords: Social Work; Kidney Failure; Social Adjustment; Psychological Support; Chronic Diseases; Quality of Life